Anticarcinogenic potential of Withania coagulans fruit against skin papilomagenesis in swiss albino mice - Mathur, Deepika; Agrawal, R C (Recent Research in Science and Technology, 2013)
Withania coagulans belongs to family Solanaceae and its beries are commonly known to be as good vegetable rennet. It has been reported to have withanolides which are known to be as a group of steroidal lactones found among members of Solanaceae. Withanolides are reported to have antitumor, antibacterial, anti-inflammatory, immune-suppressive, cyto-toxicity and antiulcer activities. In the present study, the anti-carcinogenic activity of Withania coagulans of aqueous and methanolic fruit extracts was investigated on DMBA induced skin papillomagenesis. Single topical application of 7,12-dimethylbenzanthracene (DMBA) of 100μg/100μl acetone, was given and one week later promoted by repeated application of Croton oil (1% in acetone/twice in a week ) till the end of experiment (16 weeks) in Swiss albino mice. Single topical application of Methanolic and Aqueous extract of Withania coagulans at the dose 1000mg/kg body weight along with DMBA+ Croton oil was found effective in decreasing cumulative no. of papillomas, tumor yield, tumor incidence and tumor burden as compared to the Control group i.e. DMBA and Croton oil. Histo-pathological studies also showed positive results of the Withania coagulans extracts against DMBA as promoter and Croton oil as stimulator of causing papillomagenesis. Histological sections in all the groups show marked papillomatosis, hypergranulosis and hyperkeratosis with papillary projections but in the control group papilloma consisted of fibro-vascular core with lump of epithelia showing mild dysplasia, the signs of malignancy were prominent showing Keratinous pearl and full thick dysplasia containing fibro-vascular core with lining epithelia. The tumor incidence in methanolic extract group are found statistically significant (p<0.05) in comparison to control group.